1992
DOI: 10.1002/jcla.1860060402
|View full text |Cite
|
Sign up to set email alerts
|

laboratory diagnosis of parvovirus B19 infection

Abstract: The sensitivity and application of the polymerase chain reaction (PCR) for the diagnosis of parvovirus B19 (B19) infection was investigated by simultaneously assaying a collection of 279 consecutively received samples for presence of anti-B19 IgM and IgG antibodies by Western blot and for B19 DNA by PCR and dot-blot hybridization (dot-blot); samples were sera from patients with suspected B19 infection. PCR and dot-blot detected B19 DNA in 9% (16/179) and 1% (2/179), respectively of Ab-positive samples (IgM+/Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…4,5 We report the case of an immunocompetent 10-year-old girl who developed refractory status epilepticus owing to human parvovirus B19 encephalitis. 7 In these individuals, IgM seroconversion is usually considered the best method of establishing acute or recent parvoviral infection because it has a sensitivity of 89% and a specificity of 100%. 6 Barah and coworkers reported that the incidence of undiagnosed meningoencephalitis in children that can be attributed to human parvovirus B19 infection during an outbreak year in the United Kingdom was 4.3%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 We report the case of an immunocompetent 10-year-old girl who developed refractory status epilepticus owing to human parvovirus B19 encephalitis. 7 In these individuals, IgM seroconversion is usually considered the best method of establishing acute or recent parvoviral infection because it has a sensitivity of 89% and a specificity of 100%. 6 Barah and coworkers reported that the incidence of undiagnosed meningoencephalitis in children that can be attributed to human parvovirus B19 infection during an outbreak year in the United Kingdom was 4.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) can be used to detect human parvovirus B19 DNA, but it is not necessarily a better diagnostic tool than serology in most immunocompetent patients owing to its low sensitivity. 7 In these individuals, IgM seroconversion is usually considered the best method of establishing acute or recent parvoviral infection because it has a sensitivity of 89% and a specificity of 100%. 2,8,9 In our patient, although human parvovirus B19 DNA analysis could not be performed because we detected initially high titers of serum-specific IgM and later disappearance of IgM and persistence of IgG antibodies for 3 months, the diagnosis of acute human parvovirus B19 infection was made.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, for the prenatal diagnosis of B19 infection in fetuses, a variety of virological methods have been applied to detect B19 parvovirus and B19 nucleic acid in different fetal specimens (19,20,(28)(29)(30)34), since specific IgG can represent passively acquired maternal immunity and IgM can be absent even in the presence of viral markers of B19 infection. Therefore, accurate laboratory diagnosis of B19 infection is essential in cases of nonimmune fetal hydrops both for the diagnostic value and for consideration of fetal treat-ment with intrauterine blood transfusions (26).…”
mentioning
confidence: 99%
“…Diagnosis of B19 relies on serology and the detection of viral DNA [13]. We chose polymerase chain reaction (PCR) rather than serology as a detection method because of its high sensitivity and specificity [14], low cross-reactivity (especially with rubella and rheumatoid arthritis) [1516], and ability to detect both acute and persistent B19 infections [17]. …”
Section: Introductionmentioning
confidence: 99%